Oneself as Another: Intersubjectivity and Ethics in Alzheimer’s Illness Narratives - Burke, Lucy (Narrative Works, 2014)
This paper considers what is at stake in telling the story of another’s illness and in taking on the history of another’s dementia as part of one’s own life narrative. Through a close analysis of Michael Ignatieff’s Scar Tissue, it explores the ways in which writing about the experience of caring for a parent with dementia speaks to the intersubjective dimensions of selfhood but also complicates the ways in which the very concept of intersubjectivity is often evoked within scholarship on personhood. It argues that an engagement with this kind of narrative is illuminating in this context because it exposes some of the emotional, memorial, and ethical difficulties that attend the experience of writing for and about another person when he or she is no longer able to do so.